Cocrystals of the green fluorescence protein chromophore analogue: coformer-induced switch between AIE and ACQ - Suresh, Sneha; Dabke, Niteen B.; Pandya, Rinu; Vanka, Kumar; Dutta, Madhusudan; Gonnade, Rajesh G. (Crystal Growth & Design, 2025)
Fluorescent organic solids hold great potential for advancing photonics applications. However, tuning their solid-state photoluminescent emissions remains a significant challenge. In this study, we report the synthesis and characterization of five cocrystals (two cocrystal polymorphs) derived from a pristine imidazolinone derivative (A) and the various coformer molecules, namely 1,2,4,5-tetrafluoro-3,6-diiodobenzene, 1,2,4,5-tetrafluoro-3,6-dibromobenzene, perfluoronaphthalene, and 3,4,5-trifluorobenzoic acid. The structural and optical properties of these cocrystals were examined by using single-crystal X-ray diffraction, absorption spectroscopy, photoluminescence spectroscopy, and photoluminescence decay spectroscopy. Cocrystals I, II, and III are isomorphous pairs and exhibit three-dimensional isostructurality, where the coformer molecules bridge adjacent helices of compound A, leading to aggregation-induced emission. In contrast, the cocrystal polymorphs IVA and IVB developed using coformer 3,4,5-trifluorobenzoic acid form two-dimensional sheet-like structures mediated by pi-stacking interactions between the coformers and molecule A, with interplanar distances ranging from 3.2 to 3.5 & Aring;. These stronger pi-pi interactions promote nonradiative decay pathways, resulting in reduced or quenched fluorescence and an aggregation-caused quenching effect. To gain further insights into their electronic properties, theoretical analysis including frontier molecular orbitals, time-dependent density functional theory, Hirshfeld surface analysis, molecular electrostatic potential, and noncovalent interaction plots were performed.

Steric hindrance modulated efficient thermally activated delayed fluorescence with non-linear optical, ferroelectric and piezoelectric properties - Dutta, Madhusudan; Chatterjee, Abhijit; Deka, Nilotpal; Tanwar, Riteeka; Mishra, Vishnu; Saha, Arindam; Mandal, Pankaj; Boomishankar, Ramamoorthy; Hazra, Partha (Chemical Science, 2025)
Multi-carbazole-based benzonitrile systems are efficient thermally activated delayed fluorescence (TADF) materials for organic light-emitting diodes (OLEDs). However, they suffer from low PLQY due to the large dihedral angle arising from steric crowding. Addressing this challenge, we demonstrate a potent strategy to engineer steric crowding in this work. To achieve our goal, we have designed three luminogens, namely, CzPHCN, tCzPHCN and Cz2CzPHCN based on phenanthrene-9,10-dicarbonitrile (PHCN), as an acceptor core to minimize the steric hindrance between the donor groups. Among the three luminogens, tCzPHCN exhibits a maximum PLQY of 86% and the highest RISC rate of 3.5 x 105 s-1, the underlying cause being the least dihedral angle of 45.72 degrees and suppressed intermolecular interaction due to the presence of the bulky tert-butyl group. Interestingly, our QM/MM calculations and experimental evidence suggest that the RISC process of both CzPHCN and tCzPHCN takes place via a hot exciton channel. Unlocking a new realm of applications, the unique non-centrosymmetric space group (Cmc21) of CzPHCN offers excellent SHG with a chi(2) value of 0.21 pm V-1 at 1320 nm. In addition to this, the molecule depicts good ferroelectric (PS = 0.32 mu C cm-2), piezoelectric energy harvesting (VOC = 2.8 V) and two-photon absorption properties.